Measles surveillance in Victoria, Australia - Wang Yung-Hsuan J; Andrews Ross M; Lambert Stephen B (The World Health Organization, 2006)
OBJECTIVE: Many countries are implementing measles elimination strategies. In Australia, the State of Victoria has conducted enhanced measles surveillance since 1997 using case interviews and home-based specimen collection for laboratory confirmation. We attempted to identify features of notified cases that would better target surveillance resources. METHODS: We retrospectively classified notifications received from 1998 to 2003 as having been received in an epidemic (one or more laboratory-confirmed cases) or an interepidemic period (no laboratory-confirmed cases). We labelled the first case notified in any epidemic period that was not laboratory-confirmed at the time of notification as a "sentinel case". To maximize detection of sentinel cases while minimizing the follow-up of eventually discarded notifications, we generated algorithms using sentinel cases and interepidemic notifications. FINDINGS: We identified 10 sentinel cases with 422 interepidemic notifications from 1281 Victorian notifications. Sentinel cases were more likely to report fever at rash onset (odds ratio (OR) 15.7, 95% confidence interval (CI) CI: 2.1-688.9), cough (OR 10.4, 95% CI: 1.4-456.7), conjunctivitis (OR 7.9, 95% CI: 1.8-39.1), or year of birth between 1968 and 1981 (OR 31.8, 95% CI: 6.7-162.3). Prospective application of an algorithm consisting of fever at rash onset or born between 1968 and 1981 in the review period would have detected all sentinel cases and avoided the need for enhanced follow-up of 162 of the 422 eventually discarded notifications. CONCLUSION: Elimination strategies should be refined to suit regional and local priorities. The prospective application of an algorithm in Victoria is likely to reduce enhanced measles surveillance resource use in interepidemic periods, while still detecting early cases during measles outbreaks.